KESALAHAN PENGGUNAAN TANDA BACA PADA TUGAS MATA KULIAH BAHASA INDONESIA DI SEMESTER I PG PAUD INSTITUT PENDIDIKAN NUSANTARA GLOBAL - Agus Darma Putra (JURNAL ASIMILASI PENDIDIKAN, 2024)
Punctuation errors in Bahasa course assignments are very common. These errors occur when assignments are given, many learners or students do not pay close attention to the punctuation used in their writing. That is why many punctuation marks used by students are not in the right place. The purpose of this study is to explain the errors in the use of punctuation in Bahasa Indonesia course assignments in the first semester of PG PAUD Institut Pendidikan Nusantara Global. While the method used in this study is a descriptive method with a qualitative approach. The results of this study indicate that many students make mistakes in using punctuation in Bahasa Indonesia course assignments. Based on the results of data analysis conducted by the researcher, the results of this study on punctuation errors in Bahasa course assignments are: (1) errors in the use of commas (,); (2) errors in the use of periods (.); (3) errors in the use of quotation marks (“); and (4) apostrophes.